On the Strength of Children's Right to Bodily Integrity: The Case of Circumcision. Issue 1 (24th May 2017) - Mazor, Joseph
Abstract: This article considers the question of how much weight the infringement of children's right to bodily integrity should be given compared with competing considerations. It utilises the example of circumcision to explore this question, taking as given this practice's opponents' view of circumcision's harmfulness. The article argues that the child's claim against being subjected to (presumably harmful) circumcision is neither a mere interest nor a right so strong that it trumps all competing interests. Instead, it is a right of moderate strength. Indeed, even the aggregate strength of children's rights against the practice of (presumably harmful) circumcision as a whole is not so weighty so as to always trump competing interests. The harms are not sufficiently serious to justify such a status. And the expressive wrongs associated with non‐negligently benevolent harming are much less serious than those associated with intentional harming. The debate over banning circumcision thus cannot be conducted only in terms of competing rights. Competing interests, such as those that would be set back by the departure of religious citizens, should be considered as well and might plausibly justify allowing even a rights‐infringing practice to continue.